Construction and optimization of ecological security patterns in the songnen plain - Liu, Jiping; Chen, Baolong; Zhang, Meng; Wan, Daiji; Liu, Xuan (Frontiers in Environmental Science, 2024)
To address the ecological security issues in the Songnen Plain, this study constructs the ecological security pattern by using the Multi-Criteria Evaluation Method, Minimum Cumulative Resistance (MCR) model, and Circuit Connectivity Model. Results show that: 1) The ecological source areas were 66, 52, and 56 blocks in 2000, 2010, and 2020 respectively, which are composed mainly of forests, water bodies, and wetlands. The distribution of resistance values of the ecological resistance surface shows a gradually increases trend from the source areas to the outward surrounding regions. The high and low value areas are more dispersed, consisting with the overall spatial distribution; 2) The numbers of ecological corridors show a temporal declining trend from 178 in 2000 to 159 in 2020 with a reduction of 645.46 km in total length. Node areas are mainly distributed in the southwestern and central-eastern regions and its number decreased from 232 in 2000 to 229 in 2020. The sizes of obstacle areas are 74029.52 km 2 , 70203.72 km 2 , and 75529.72 km 2 in the three periods; 3) The size of important ecological source areas has decreased by 5779.16 km 2 , the area of medium ecological source areas has increased by 11466.44 km 2 , and the area of general ecological source areas has increased by 9509.16 km 2 . The areas being classified as ecological conservation, ecological enhancement, ecological restoration, and ecological control are 30346.68 km 2 , 8480.56 km 2 , 51473.92 km 2 , and 122047.48 km 2 , respectively. The multiple spatial pattern optimization strategies are proposed based on the identified ecological source areas, corridors, node points, and other comprehensive ecological security patterns. It not only provides practical reference for the ecological restoration and ecological protection in the Songnen Plain, but also can be used for the ecological security pattern investigations in other study regions in the world.